PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR-DASAR KONSTRUKSI - Aldy Ayusya; Revian Body (Teknik Sipil Universitas Negeri Padang, 2021)
Abstract: This research is motivated by the still low learning outcomes of the Class X Construction Basics Subject of SMKN 5 Padang, caused by the use of methods in the learning process that are less varied so that learning is quite boring so that students are less active when the learning process only listens to what is said. by teachers and in the end have an impact on the low learning outcomes obtained by students. This study aims to determine (1) the effect of learning outcomes in construction basics that are taught using the STAD cooperative learning model in class X DPIB students. (2) Differences in learning outcomes in the construction basics subject that are taught using the STAD cooperative learning model and those using conventional learning models in class X DPIB students. Using the experimental research method, Quasi-Experimental design uses two classes, namely experiment and control. Data obtained from the posttest results to measure student learning outcomes. The analysis was carried out by testing the hypothesis, namely the t-test. The results obtained (1) There is a significant influence between the learning outcomes of the subjects of construction basics in the experimental class taught using the STAD cooperative learning model with the control class using conventional learning models, with tcount (7,196)> ttable (1.70562) at α(sig 2 tailed) 0.000 <0.05. (2) There are differences in learning outcomes in the construction basics of class X DPIB students who are taught using the STAD cooperative learning model with the conventional learning model with an average value of the experimental class of 80.46 and the control class of 76.92.